(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
The contemporary landscape of preschool education is characterized by an accelerating demand for educators capable of fostering complex cognitive development, emotional regulation, and creative problem-solving in children from the earliest stages of human formation. This article addresses the persistent disconnect between the academic preparation of future preschool teachers and the multidimensional intellectual demands of contemporary early-childhood pedagogy, and proposes the development of an Integrated Intellectual Competence Framework as a strategic mechanism for the comprehensive professional formation of educators.